Contributing Factors for Perceived Satisfaction with Nursing Care among Inpatients in General Wards - Koirala, Mamta; Koirala, Mohan Laxmi (Journal of Lumbini Medical College, 2016)
Introduction: Patients' perceived satisfaction with quality of care may affect health outcomes. Patients who are satisfied with their nursing care are more likely to follow treatment and consequently to have better health outcomes. It encourages them to behave in a healthy way after discharge, and positive rating of service quality seems to be correlated with no hesitation about revisiting the same hospital ward in time of need. This study was done to identify the contributing factors for perceived satisfaction with nursing care among inpatients in general wards in Lumbini Medical College. Methods: A descriptive cross sectional study was conducted in Lumbini Medical College Teaching Hospital throughout the month of August, 2015. A total of 60 heterogeneous study population from three different wards (Medical, Surgical, and Orthopedics), who gave consent for participation, were included using non-probability convenient sampling technique. Nepalese version of Newcastle Satisfaction with Nursing Scale (NSNS) was used to measure the satisfaction score. Results: There were a total of 60 respondents with mean age of 30.08 years (SD= 9.72). Male, duration of hospital stay, and number of hospital stay had a significant relation with the satisfaction score when calculated individually. However, the relationship was not significant when adjusted for other variables by linear regression. Conclusion: Majority of respondents were satisfied with the quality of nursing care. Male, duration of hospital stay, and number of hospital admission had a significant relation with the satisfaction score when calculated individually. The nurses should know the factors influencing patients' satisfaction and work on those to improve the quality of nursing care. DOI: https://doi.org/10.22502/jlmc.v3i2.69 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015, page 34-37